2012
DOI: 10.1117/1.jbo.17.12.125006
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic ultrasound spectroscopy for assessing red blood cell aggregation and oxygenation

Abstract: Abstract. Red blood cell (RBC) aggregation and oxygenation are important markers for a variety of blood disorders. No current technique is capable of simultaneously measuring aggregation/oxygenation levels noninvasively. We propose using photoacoustic ultrasound spectroscopy (PAUS) for assessing both phenomena. This technique relies on frequency-domain analysis of the PA signals by extracting parameters such as the ultrasound spectral slope and the midband fit. To investigate the effect of hematocrit, aggregat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 44 publications
7
66
0
Order By: Relevance
“…15 The validity of the prediction was confirmed by conducting in vitro experiments with human and porcine RBCs. 16,17 The framework was also used to investigate the PAs of mixtures of oxygenated and deoxygenated RBCs and provided results consistent with that of experiments. 18 The possibility of using the PA technique to differentiate intraerythrocytic stages of malarial parasite was examined using this theoretical tool.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…15 The validity of the prediction was confirmed by conducting in vitro experiments with human and porcine RBCs. 16,17 The framework was also used to investigate the PAs of mixtures of oxygenated and deoxygenated RBCs and provided results consistent with that of experiments. 18 The possibility of using the PA technique to differentiate intraerythrocytic stages of malarial parasite was examined using this theoretical tool.…”
Section: Introductionmentioning
confidence: 65%
“…Recent experimental studies also reported that these parameters can influence PA spectral characteristics. 17,[22][23][24] These theoretical and experimental findings essentially opened up a possibility that tissue characterization might be feasible with PAs. Wang et al accurately assessed the dimensions of microparticles hidden in turbid phantoms using a spatial auto-correlation function to perform PA spectral analysis.…”
Section: Introductionmentioning
confidence: 95%
“…The resultant power spectra from different elements are presented in Figure 1d. The power spectra were normalized to a reference (Figure 1e) to reduce the effect of the transducer bandwidth on calculated spectral parameters [18], [21]. The reference sample was prepared using a 200 nm layer of gold mounted on top a microscopy slide with a 10 nm of chromium to strengthen the adhesion of the gold to the glass slide.…”
Section: Pa Signals Acquisitionmentioning
confidence: 99%
“…A reference is used to reduce the effect of the transducer to attain system independent parameters [16], [17]. These approaches have provided information about the size and shape of the ultrasound source at scales smaller than the working wavelength of the system [18]- [20]. The information can be related to the dimension, distribution and concertation of the ultrasound sources which, in the case of PA imaging, are RBCs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies by our group [12,13], the PA measurement of SO 2 and EA was preliminarily conducted under the static conditions. In order to further advance the clinical applicability of PA imaging, the SO 2 and EA should be investigated simultaneously under flowing conditions.…”
Section: Introductionmentioning
confidence: 99%